Identity Strategy On Instagram Social Media: How Dian Sastrowardoyo Faces Privacy And Surveillance Challenges : Strategi Identitas Pada Media Sosial Instagram: Bagaimana Dian Sastrowardoyo Menghadapi Tantangan Privasi dan Pengawasan - Wildan Bisma Radiyan; Moch. Nur Faizin (Universitas Muhammadiyah Sidoarjo, 2025)
This research explores how public figures, particularly Dian Sastrowardoyo, shape their online identities on Instagram and manage context collapse, as well as the risks and opportunities faced related to privacy and surveillance. Using the content analysis method pioneered by Harold D. Lasswell and netnography, the data was collected through online observation and content analysis from Dian Sastrowardoyo's Instagram account. The results show that Dian uses Instagram to form an online identity consistent with her public image as an actress and activist, with key patterns such as image consistency, social activism, and limited personal life. In managing context collapse, Dian uses strategies such as audience segmentation, curated content, and the use of different languages. The research also identified significant privacy risks, including the potential for misuse of personal information and surveillance by media and fans, as well as opportunities to expand influence and reach a wider audience. With the right strategy, Dian can manage these risks and take advantage of the opportunities that exist to strengthen her online identity. This research provides in-depth insights into the dynamics of online identities and privacy challenges in the digital era, as well as the importance of the right strategies in managing online identities and maintaining privacy on social media.